PENGARUH MODEL THINK TALK WRITE BERBANTUAN SOFTWARE GEOGEBRA TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SEKOLAH DASAR - Oktaviani, Anti; Rahayu, Puji; Mustikaati, Wina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the infuence of Think Talk Write model assisted by Geogebra Software on mathematical understanding ability of elementary school students. The Think Talk Write model can help students understand a concept through the process of thinking, talking, and writing so that students are actively involved in the learning process, while Geogebra Software provides a visual experience so that students can visualize abstract mathematical concepts into a real form that is easy to understand. This research was conducted in grade V elementary school with the type of research Quasi Experiment and research design Noneequivalent Control Group Design. The samples used were two classes, namely class VA as an experimental class using the Think Talk Write model assisted by Geogebra Software and VB as a control class using the Cooperative Learning Type Make a Match model. The results of this study indicate that students in the experimental class have better results seen from the difference in the average posttest score compared to the control class. The research instrument used is a description question. In inferential data with a simple linear regression test, the results of the effect of the Think Talk Write model assisted by Geogebra Software on students' mathematical understanding skills were 80%. Thus, this study can be concluded that learning with the Think Talk Write model assisted by Geogebra Software has an influence on students' mathematical understanding skills.